8th International conference on cell & stem cell engineering (ICCE) - El Haj, Alicia; Bader, Dan (IFMBE proceedings, 2011)
This volume presents selected peer-reviewed papers of the 8th International Conference on Cell & Stem Cell Engineering (ICCM) 2010 in Dublin. The contributions are written by leading scientists in Cell and Stem Cell Engineering and the topics of the papers include: Computational Cell Mechanics Experimental techniques in Cell Mechanics Molecular and Cell Imaging Cell Matrix Interactions Mechanotransduction and cell mechanics Cell sensing Cell processing Artificial cells Stem cell niche Cell Networks